2016
DOI: 10.1007/s11914-016-0302-7
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis Associated with Epilepsy and the Use of Anti-Epileptics—a Review

Abstract: The increased rate of fractures associated with epilepsy has been long recognised but remains incompletely understood. Study quality and study results have varied, with some but not all studies showing bone diseases including osteoporosis and/or osteomalacia, and a high prevalence of vitamin D insufficiency and deficiency are also noted. Falls risk can also be higher in patients with epilepsy taking anti-epileptic medications, potentially leading to fracture. Larger research collaborations are recommended to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 124 publications
(151 reference statements)
0
43
0
4
Order By: Relevance
“…Also, another study from Nettekoven et al indicated that epilepsy is related with increased bone turnover although physical activity levels were not assessed during their study [29]. Bone biopsy studies in epileptic patients who sustained a fracture have found reduced bone formation and resorption, an increase in the size of haversian canals and an increased resorption of trabecular bone, a degree of osteoporosis, and also increased deposition of osteoid which is suggestive of osteomalacia [17,30].…”
Section: Aeds and Bone Cells And Bone Turnovermentioning
confidence: 98%
See 4 more Smart Citations
“…Also, another study from Nettekoven et al indicated that epilepsy is related with increased bone turnover although physical activity levels were not assessed during their study [29]. Bone biopsy studies in epileptic patients who sustained a fracture have found reduced bone formation and resorption, an increase in the size of haversian canals and an increased resorption of trabecular bone, a degree of osteoporosis, and also increased deposition of osteoid which is suggestive of osteomalacia [17,30].…”
Section: Aeds and Bone Cells And Bone Turnovermentioning
confidence: 98%
“…According to another study by Babayigit et al, oxcarvazepine, carvamazepine and valproate acid have been related to reduced BMD in the lumbar spine of epileptic children which comes along with hypocalcemia, hypophosphatemia and reduced vitamin D levels [16]. Another study by Petty et al compared the BMD in 21 epileptic children and concluded that carvamazepine, compared to valproate, lessen the BMD in L1-L4 in epileptic children [17].…”
Section: Aeds and Vitamin Dmentioning
confidence: 99%
See 3 more Smart Citations